Obtaining a reference for calibrating broadband multibeam seabed backscatter multibeam seabed backscatter - Bodra, Ivan (2020)
Standard calibration procedures for multibeam sonars currently only address the fidelity of the bathymetric data. Equivalent effort is needed to ensure that the acquired seabed backscatter strength measurements are referenced to a similarly precise level. This thesis presents an operational method for acquiring reference seabed backscatter data utilizing multiple pre-calibrated split beam echo sounders covering a wide range (45-450 kHz) of frequencies. This is needed to cover the full range of frequencies utilized by multi-sector multibeam systems operating in continental shelf depths. The method considers both the frequency and the angle of incidence dependence of the backscatter strength of a homogenous seafloor region. By using a mechanically rotated plate, the split beam transducers, once calibrated, are able to collect the absolute angular response curve of the seafloor for any frequency within the bandwidth of interest. This thesis addresses the design, implementation and required processing to deliver the curves of selected areas. Although not part of this research, the next step would be to calibrate the desired multibeam echosounder for backscatter by comparing the results obtained by the systems over the same seafloor area. The results obtained, reveal one of the most complete pictures of the continuous variation of the seabed backscatter angular response from 45 to 400 kHz. Significantly, this extends well above the 100 kHz level that normally defines the upper end of surface scattering model fidelity. As the chosen sites cover the main range of expected marine sediment xv types (gravel to mud), trends in both frequency and grazing angle are apparent that might impact the choice of frequency used in multi-spectral backscatter imaging.